ENG Sarah Kofman in the debate on the existentialist morality - Riba, Jordi (Anales del Seminario de Historia de la Filosofía, 2026)
Sarah Kofman dealt with the viability of existentialist morality in her writings, although she added a plus in its epistemic acceptance. In addition to giving viability to the writings and proposals of Jean-Paul Sartre and Simone de Beauvoir, Kofman’s text reveals elements of their philosophical activity that allow them to give even more visibility to their moral work.